NILAI PENDIDIKAN DALAM HADIH MAJA MASYARAKAT DI KECAMATAN MUTIARA TIMUR, PIDIE - Nurul Aida Fitri (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This research aims to obtain a description of the hadih maja data and the educational value contained. The method used in this research is a qualitative descriptive method. Data collection techniques include observation, documentation and interviews. The data sources for this research are ten community leaders who live in Mutiara Timur District, Pidie Regency. The results of the research showed that the researchers obtained 30 hadih maja which contained various educational values, such as moral values, cultural values, social values ​​and religious values. The hadih maja referred to varies, namely hadih maja which consists of four lines, three lines, two lines, and some are also one line. There are 18 maja hadih containing moral values, 6 maja hadih containing social values, 5 maja hadih containing cultural values, and 1 maja hadih containing religious values